Physically crosslinked thermo-responsive hydrogel nanofibres with tunable hydrophobicity based on poly(N-isopropyl acrylamide)-graft-poly(dimethyl siloxane) - Kuyler, Gestél Christine (2019)
Thesis (MSc)--Stellenbosch University, 2019.